TmIKKε Is Required to Confer Protection Against Gram-Negative Bacteria, E. coli by the Regulation of Antimicrobial Peptide Production in the Tenebrio molitor Fat Body - Ko, Hye Jin; Patnaik, Bharat Bhusan; Park, Ki Beom; Kim, Chang Eun; Baliarsingh, Snigdha; Jang, Ho Am; Lee, Yong Seok; Han, Yeon Soo; Jo, Yong Hun (Frontiers in Physiology, 2022)
Inhibitor of nuclear factor-kappa B (NF-κB) kinase (IKK) is the core regulator of the NF-κB pathway against pathogenic invasion in vertebrates or invertebrates. IKKβ, -ε and -γ have pivotal roles in the Toll and immune deficiency (IMD) pathways. In this study, a homolog of IKKε was identified from Tenebrio molitor RNA sequence database (TmIKKε) and functionally characterized for its role in regulating immune signaling pathways in the insect. The TmIKKε gene is characterized by two exons and one intron comprising an open reading frame (ORF) of 2,196 bp that putatively encodes a polypeptide of 731 amino acid residues. TmIKKε contains a serine/threonine protein kinases catalytic domain. Phylogenetic analysis established the close homology of TmIKKε to Tribolium castaneum IKKε (TcIKKε) and its proximity with other IKK-related kinases. Expression of TmIKKε mRNA was elevated in the gut, integument, and hemocytes of the last-instar larva and in the fat body, Malpighian tubules, and testis of 5-day-old adults. TmIKKε expression was significantly induced by Escherichia coli, Staphylococcus aureus, and Candida albicans challenge in whole larvae and in tissues, such as hemocytes, gut, and fat body. Knockdown of TmIKKε mRNA expression significantly reduced the survival of the larvae against microbial challenges. Further, we investigated the induction patterns of 14 T. molitor antimicrobial peptides (AMP) genes in response to TmIKKε gene-silencing after microbial challenges. While in hemocytes, the transcriptional regulation of most AMPs was negatively regulated, in the gut and fat body tissue of T. molitor, AMPs, such as TmTenecin 1, TmTenecin 4, TmDefensin, TmColeoptericin A, TmColeoptericin B, TmAttacin 1a, and TmAttacin 2, were positively regulated in TmIKKε-silenced individuals after microbial challenge. Collectively, the results implicate TmIKKε as an important factor in antimicrobial innate immune responses in T. molitor.